2017
DOI: 10.2147/ndt.s145245
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in obesity and cognitive function in a cognitively normal aging Chinese Han population

Abstract: BackgroundSex differences in Alzheimer’s disease and mild cognitive impairment have been well recognized. However, sex differences in cognitive function and obesity in cognitively normal aging Chinese Han population have not attracted much attention.ObjectiveThe aim of this study was to investigate the relationship between sex, obesity, and cognitive function in an elderly Chinese population with normal cognitive function.Subjects and methodsA total of 228 cognitively normal aging participants (males/females =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…In a study among of Chinese older adults aged 90 years and over (3), the prevalence of cognitive impairment increased to 57.8% overall and up to 67.2% among women. Other studies have shown similar results (4) (5) . These inconsistencies might be attributable to gender-and age-related differences in blood lipid pro les, aetiology of dementia and methods of cognitive assessment (2,6).…”
Section: Introductionsupporting
confidence: 76%
“…In a study among of Chinese older adults aged 90 years and over (3), the prevalence of cognitive impairment increased to 57.8% overall and up to 67.2% among women. Other studies have shown similar results (4) (5) . These inconsistencies might be attributable to gender-and age-related differences in blood lipid pro les, aetiology of dementia and methods of cognitive assessment (2,6).…”
Section: Introductionsupporting
confidence: 76%
“…In a study among of Chinese older adults aged 90 years and over [3], the prevalence of cognitive impairment increased to 57.8% overall and up to 67.2% among women. Other studies have shown similar results [4,5] . These inconsistencies might be attributable to gender-and age-related differences in blood lipid profiles, aetiology of dementia and methods of cognitive assessment [2,6].…”
Section: Introductionsupporting
confidence: 69%
“…Participants may have had alterations in their energetic profile as a result of weight loss, reduced caloric intake, and increased energy requirements, while low lipid levels might have reflected malnutrition in subjects with cognitive impairment . Accumulating evidence suggests that lipid levels are associated with cognitive function and dementia, but studies have shown that the association between lipid levels and cognitive function might be complicated by and related to sex, age, and specific cognitive domains . These inconsistent results and potential relationships triggered our interest in exploring the cognitive function’s association with BMI and serum lipids in the elderly population.…”
Section: Introductionmentioning
confidence: 99%